Techno-economic evaluation of sorption enhanced steam gasification of PKS system for syngas using CaO for CO2 capture - Shahbaz, M. (Elsevier B.V., 2021)
Biomass Gasification is a viable process to convert biomass into valuable energy production. In this study, the techno-economic feasibility of a sorption enhanced steam gasification of palm oil waste for syngas production is developed using Aspen Plus. The sorption enhancement is achieved by utilising CaO as a medium to capture CO2 and generate clean syngas. CaO has recently demonstrated the feasibility to capture CO2 at reduced capital and operating investment costs compared to conventional capture processes. For this purpose, the flowsheet configuration and economic analysis has been carried out using Aspen plus. The results of the economic assessment demonstrate a total hydrogen production cost approximated at 2.51 per kg for gasification system utilising CaO compared to 2.57 for the base case without CO2 capture. Moreover, a sensitivity analyses and a multi-objective optimisation has been carried out to maximise the hydrogen to carbon monoxide ratio and minimise the CO2 emissions. The results demonstrate that by increasing the steam flowrate in the range of 500-2000 kg/h, the H2/CO ratio, and the CO2 emissions increase. This is mostly due to the acceleration of gasification reactions; mainly the methane reforming and water gas shift reactions. Similarly, increasing the CaO flowrates in the range of 500-2000 kg/h results in increasing the H2/CO ratio significantly and reducing the CO2 emissions rapidly. This CO2 reduction with the use of CaO is experimentally validated in the literature mainly due to the carbonation reaction. Whereas, the variation of gasification temperature indicates a decreasing trend in the H2/CO ratio and CO2 emissions with the increase in temperature in the range of 600-800 oC. The Pareto curve generated from the multi-objective optimisation demonstrates an overall increasing trend of CO2 emissions with the increase in the H2/CO ratio in the produced syngas. Â© 2021 Elsevier B.V.